2011
DOI: 10.1007/s10509-011-0748-0
|View full text |Cite
|
Sign up to set email alerts
|

Dust-ion-acoustic solitary waves and their multi-dimensional instability in a magnetized dusty electronegative plasma with trapped negative ions

Abstract: A theoretical investigation has been made on obliquely propagating dust-ion-acoustic solitary waves (DIASWs) in magnetized dusty electronegative plasma containing Boltzmann electrons, trapped negative ions, cold mobile positive ions, and arbitrarily charged stationary dust. The reductive perturbation method has been employed to derive the modified Zakharov-Kuznetsov (MZK) equation which admits solitary wave solution under certain conditions. The multi-dimensional instability of these solitary waves is also stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 41 publications
(39 reference statements)
3
11
0
Order By: Relevance
“…To study the properties of the SWs propagating in the present system we follow the same procedure as [15] to get the steady state solution of the well-known mZK equation. Therefore, after some iterative mathematical calculation (not shown here), one can obtain:…”
Section: Sw Solution Of the Mzk Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the properties of the SWs propagating in the present system we follow the same procedure as [15] to get the steady state solution of the well-known mZK equation. Therefore, after some iterative mathematical calculation (not shown here), one can obtain:…”
Section: Sw Solution Of the Mzk Equationmentioning
confidence: 99%
“…Sayed et al [14] have studied the DIASWs in an unmagnetized multi-ion dusty plasma containing inertia-less isothermal electrons, cold inertial positive and negative ions, and negatively charged static dust. Rahman et al [15] have theoretically studied the basic properties (phase speed, amplitude, and width) and multidimensional instability of the obliquely propagating DIASWs in a magnetized four components dusty electronegative plasmas which contains isothermal electrons, non-isothermal trapped negative ions, cold mobile positive ions, and arbitrarily charged stationary dust by deriving mZK equations instead of usual ZK equations due to trapped negative ions. Kundu et al [16] have investigated the nonlinear propagation of the obliquely propagating DIASWs and multidimensional instability in a four-component magnetized dusty electronegative plasmas and found that the effects of nonthermal negative ions significantly modify the nature of the DIASWs structures in a dusty plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, they may follow a vortex-like distribution [34], which affect drastically on the nonlinear propagation mode. Some recent theoretical studies focused on the effects of ion and electron trapping which is common not only in space plasmas but also in laboratory experiments [1,30,37]. El-Wakil et al [11] theoretically investigated higher order contributions to nonlinear DA waves that propagate in a mesospheric dusty plasma with a complete depletion of the background (electrons and ions).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of trapped ions can significantly modify the wave propagation characteristics in collisionless plasmas, so one considers vortex-like ion distributions in phase space instead of the usual Boltzmann law (Schamel 1982;Schamel et al 2001). Some recent theoretical studies focused on the effects of ion and electron trapping which is common not only in space plasmas but also in laboratory experiments (Schamel 1972(Schamel , 1975Mamun et al 1996;Shchekinov 1997;Rahman et al 2011;Alinejad 2012;El-Labany et al 2012). However, the effects of vortex-like ion distribution on nonlinear DA solitary and shock waves in a strongly coupled dusty plasma or in a magnetized dusty plasma were examined (Mamun 1998;Mamun et al 2004;Anowar et al 2009).…”
Section: Introductionmentioning
confidence: 99%